THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZED MARKETING (International Journal of Food and Nutritional Sciences, 2022)
Marketing is undergoing a sea change as a result of AI's ability to provide targeted, personalised interactions with customers. This study delves into the significance of artificial intelligence (AI) in tailored marketing approaches, highlighting its uses, advantages, and consequences for companies. Consumers in today's competitive market want customised experiences and relevant material, which is why personalised marketing is becoming more important, as the abstract explains. Next, it explores how AI is being used in personalised marketing using tools like recommendation engines, natural language processing, machine learning, and predictive analytics. In addition, the abstract goes over some of the advantages of AI-driven personalised marketing, including higher conversion rates, happier customers, more engagement, and a better return on investment. It delves into the ways in which AI algorithms sift through mountains of data in order to create segments of audiences, forecast customer actions, and broadcast timely, relevant messages via specific channels.